2009
DOI: 10.1007/s10551-009-0168-z
|View full text |Cite
|
Sign up to set email alerts
|

How do Small and Medium Enterprises Go “Green”? A Study of Environmental Management Programs in the U.S. Wine Industry

Abstract: energy conservation, environmental management systems, recycling, small and medium enterprises, stakeholder pressures, Theory of Planned Behavior,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
153
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(169 citation statements)
references
References 28 publications
(49 reference statements)
10
153
2
4
Order By: Relevance
“…Whether the change in the traders' behavior came about because they believed this behavior was the 'right thing to do' (Jenkins, 2009), or whether it was because there was a tangible consequence to not complying (i.e., social censure), compliance occurred. This pathway from innovation to normality (Fell et al, 2009) reflects Jackson's (2005) view that social norms reprimand or encourage certain behavioral choices among groups, while also serving as cultural rules, fostering emotionally fulfilling social and socially-embedded market relationships (Cordano et al, 2010;Varman and Costa, 2008). Gaining commitment from the majority of the retailers established community norms (i.e.…”
Section: The Case Of Modbury Devonmentioning
confidence: 90%
See 1 more Smart Citation
“…Whether the change in the traders' behavior came about because they believed this behavior was the 'right thing to do' (Jenkins, 2009), or whether it was because there was a tangible consequence to not complying (i.e., social censure), compliance occurred. This pathway from innovation to normality (Fell et al, 2009) reflects Jackson's (2005) view that social norms reprimand or encourage certain behavioral choices among groups, while also serving as cultural rules, fostering emotionally fulfilling social and socially-embedded market relationships (Cordano et al, 2010;Varman and Costa, 2008). Gaining commitment from the majority of the retailers established community norms (i.e.…”
Section: The Case Of Modbury Devonmentioning
confidence: 90%
“…SMEs also tend to rely on informal networks for information (Rothenberg and Becker, 2004), for example, local trade associations, reaffirming a role for social influence variables such as attitudes and norms on the adoption of sustainable decision making (Cordano et al, 2010). Southwell (2004) identified that SMEs believe they should pay significant attention to their social and environmental responsibilities.…”
Section: The Owner-manager As 'Champion'mentioning
confidence: 98%
“…There is also evidence suggesting that SMEs do not welcome environmental regulations (Brammer et al, 2012;Cordano et al, 2010;Lewis and Cassells, 2010;Wilson et al, 2012), primarily because of the complexities and costs attached with their observance (Simpson et al, 2004;Wilson et al, 2012). Moreover, research from some developing countries, like Pakistan and China, also refers to weaker implementation of environmental regulations reducing SMEs compliance (Wahga et al, 2015;Yu and Bell, 2007).…”
Section: Environmental Regulationsmentioning
confidence: 99%
“…This implies that if owner-managers are personally considerate towards the natural environment, it is highly likely that they would introduce environmentally friendly practices in their businesses (Cambra-Fierro et al, 2008;Cordano et al, 2010;Font et al, 2016;Hemingway and Maclagan, 2004). There is evidence that, in some SMEs, the environmental values of owner-mangers have induced the adoption of sustainable practices (e.g.…”
Section: Entrepreneurs' Moral Valuesmentioning
confidence: 99%
“…Les travaux traitant des motivations écologiques ne manquent pas (Lansiluoto et Jarvenpaa, 2008 ;Cordano, Marschall et Silverman, 2010). Néanmoins, ces travaux supposent l'existence de trois principales motivations : les motivations relationnelles, économiques et éthiques.…”
Section: Cadre Théoriqueunclassified